Challenges in Applying Night Work Norms in Indonesia - Rio Arif Pratama; Bayu Prasetyo (Universitas Muhammadiyah Sidoarjo, 2019)
Everyone has the right to have and determine the desired work, get a fair treat and get a decent wage, it is governed by the Constitution of the Republic of Indonesia. In general, working in the morning until evening, but there is also work carried out at night. The lawmakers pay special attention to the execution of work at night by providing a number of excusive rights as part of legal protection for workers. This research aims to determine the opportunities and challenges of applying the night work norms based Law No. 13 of 2003 on legal systems through legal substance, legal structure and legal culture analysis in the field of employment. TThe results of the research are in several Indonesian Regions there are still similar challenges regarding the implementation of night work norms. The authors also assess there are a number of opportunities for improvement in order for nighttime work norms to run well.